Peran Guru Pendidikan Agama Islam dalam Meningkatkan Kualitas Keagamaan Siswa Kelas XII di SMK Swasta Wira Jaya Tanjung Morawa - Anggi Tryana; Khairuddin Lubis; Armanila Armanila (Fakultas Agama Islam Universitas Al Washliyah, 2025)
This research examines the role of Islamic Religious Education (IRE) teachers in improving the religious quality of Grade XII students at SMK Swasta Wira Jaya Tanjung Morawa. The study was conducted using a qualitative approach through interviews, observations, and documentation involving IRE teachers and students from four different majors. The findings reveal that IRE teachers carry out eight main roles, namely as educators, teachers, counselors, role models, motivators, facilitators, inspirators, and evaluators. Students' religious quality is influenced by internal factors such as personal interest and dedication, as well as external factors including the role of family, the school environment, and peer associations. Regular religious activities at school, teachers' exemplary conduct, and family support serve as the main pillars in shaping students' religious character.